Comparison between Immediate Effects of MET and Passive Stretching Techniques on Hamstring Flexibility in Patients with Hamstring Tightness: An Experimental Study - Samiksha Sanjiv Sathe1 , Tejal Rajandekar2 , Kirti Thodge3 , Vasant Gawande4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Muscular flexibility is an important part of functioning of human being and hamstringmuscle is prominently found to be tight in human body. Hamstring muscle flexibility can be improved bya variety of stretching method and other techniques, yet very little work has been done to compare muscleenergy technique (MET) and passive stretching techniques. The objective of our study was to compare theimmediate effectiveness of muscle energy technique (MET) and Passive stretching on hamstring flexibilityin individuals with hamstring tightness.Method: 42 participants who met the inclusion criteria were randomly divided into two equal groups, GroupA – MET and Group B – Passive stretching. The range of motion (ROM) of knee extension was measuredbefore and after both the techniques by AKET using universal goniometer.Results: There was a significant improvement in hamstring flexibility in both the groups following theapplication of MET and Passive stretching.Conclusion: From the present study we can conclude that both MET and passive stretching techniques havean immediate effect on reducing hamstring muscle tightness. From the mean difference values it is visiblethat MET (12.81) is slightly more effective than passive stretching (6.38) although statistically significantdifference is not seen.